International displacement and state compliance with international human rights standards: the current protection of internally displaced persons' right to physical security in Nigeria - Bjoerkan, Maren (Department of Public Law, 2018)
There are approximately 65.3 million forcibly displaced people in the world. A large majority of these people are internally displaced. Of the 40.8 million internally displaced persons' (IDPs) worldwide, Nigeria had a total of 1,955,000 IDPs at the end of 2016. Consequently, Nigeria is among the countries with the highest number of displaced persons globally. A wide range of political, economic, social, and environmental factors, including poverty, corruption, and internal armed conflict, affect the population in Nigeria and contribute to internal instability. Thus, as Nigeria represents a complex and multi-layered situation of internal displacement, it makes for an interesting case study to understand international protection of IDPs. This dissertation asks whether the current protection of IDPs' right to physical security in Nigeria complies with international human rights standards. The current international legal framework in place for the protection of IDPs is relatively extensive, and undergoes continuous development. The United Nations Guiding Principles for the Protection of Internally Displaced People and the African Union Convention for the Protection and Assistance of Internally Displaced Persons in Africa (Kampala Convention), as well as general human rights mechanisms, comprehensively set out the rights and guarantees for the protection of the physical security of IDPs. Although there has been great improvement in recent years relating to the legal protection of and assistance to IDPs, the de facto implementation and enforcement of these frameworks in Nigeria is not in full compliance with international human rights standards.